Pengaruh Rasio Likuiditas Dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Industri Makanan Dan Minuman Yang Terdaftar Di BEI - Resa Enjelina Brutu; Mila Yulia Herosian; Bella Christen Panjaitan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study plans to conclude whether liquidity generally affects industrial points in the Food and Beverage Industry Sub-Area at the Gathering Association written on the IDX. The impact mostly affects organizational points in the Food and Beverage Industry Affiliated Sub-Area listed on the BEI. Liquidity and its utilization after some time basically affect the association points in the Authority Relations of the Food and Beverage Industry Sub-Regional Authority listed on the BEI. The survey approach uses different quantitative tests. The number of examinations in the 2014-2020 investigation period was 11 affiliates. The consequence of this research shows that the liquidity hierarchy in a general sense affects most of the hierarchical qualities in Collector Relations in the Food and Beverage Industry Sub-Regions listed on the IDX. Keywords : Liquidity, Leverage and Firm Value